Penerapan Kinerja Karyawan dalam Mencapai Sasaran Mutu: (Studi pada Pegawai Non Medis Instalasi Sterilisasi di Rumah Sakit Dr. Kariadi Semarang) - Adi Setya Pamungkas; Sri Yuni Widowati; Aprih Santoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2019)
This study was motivated by the decline in targets in the Sterilization Installation of the Hospital Dr. Kariadi Semarang, for that the problem can be formulated is how the Sterilization Installation Section improves employee performance so that the production target is reached. The purpose of this study was to analyze the influence of Leadership, Work Environment and Work Discipline on Employee Performance of the Sterilization Installation at DR. Kariadi Semarang.Data were collected through questionnaire methods using Census techniques for 61 respondents in the Sterilization Installation section. Data processing uses multiple regression analysis, hypothesis testing through t test, model testing with f test, and analysis of the coefficient of determination.The results obtained in this study are the magnitude of the coefficient of determination is 0.547 which means that 54.7% of the variables of Leadership, Work Environment and Work Discipline have a positive and significant effect on Employee Performance